2022
DOI: 10.3389/fcell.2022.868918
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Stress Granule Regulators-Associated Molecular Subtypes Predicts Drug Response, Immune Response, and Prognosis in Non-Small Cell Lung Cancer

Abstract: Lung cancer has the world’s second highest cancer incidence and second highest cancer-related mortality rate. However, the mechanism underlying non-small cell lung cancer (NSCLC) remained to be unclear. Overall, this study for the first time revealed Stress Granule Regulators were mutated and dysregulated in NSCLC samples by analyzing TCGA database. Moreover, three subtypes of NSCLC were identified based on the expression levels of Stress Granule Regulators. Patients in cluster 2 showed a higher survival rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Additionally, previous studies have reported that PI3K-AKT signaling pathways could be suppressed after downregulation of EGFR in glioma, pancreatic cancer, and non-small cell lung cancer. (Milton et al, 2020;Han and Wang, 2022;Wang et al, 2022). The level of p-AKT was decreased after treatment of an EGFR antagonist (JMR-132) in ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies have reported that PI3K-AKT signaling pathways could be suppressed after downregulation of EGFR in glioma, pancreatic cancer, and non-small cell lung cancer. (Milton et al, 2020;Han and Wang, 2022;Wang et al, 2022). The level of p-AKT was decreased after treatment of an EGFR antagonist (JMR-132) in ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The method we used is similar to that reported in an earlier study we published [ 19 ]. Briefly, the gene expression profiling datasets GSE24988 [ 20 ], GSE113439 [ 21 ] and GSE117261 [ 22 ] are based on GPL6244 ([HuGene-1_0-st] Affymetrix Human Gene 1.0 ST Array [transcript (gene) version]) were downloaded from the GEO database ( https://www.ncbi.nlm.nih.gov/geo/ ).…”
Section: Methodsmentioning
confidence: 99%
“…The method we used is similar to that reported in an earlier study we published. 19 Brie y, the gene expression pro ling datasets GSE24988 20 , GSE113439 21 and GSE117261 22 are based on GPL6244 ([HuGene-1_0-st] Affymetrix Human Gene 1.0 ST Array [transcript (gene) version]) were downloaded from the GEO database (https://www.ncbi.nlm.nih.gov/geo/). The GSE24988 dataset contained 62 PH and 22 normal lung tissues.…”
Section: Data Collection and Analysis Of Differentially Expressed Genesmentioning
confidence: 99%